PENGARUH SOSIALISASI TERHADAP PERSEPSI DAN PENGETAHUAN MASYARAKAT PADA BANK SYARIAH KAB. ACEH TENGGARA - Bahrul Ilmi (EKSPOLHUM, 2025)
Islamic banks are here to help the economic welfare of the Muslim community, but there are still many Muslims who do not know about Islamic banks and many of them are still customers of conventional banks. This study aims to determine the effect of socialization, knowledge and public perception of Islamic banks on the interest in saving in Islamic banks in Southeast Aceh. This research is a qualitative research type. The data sources in this study are primary and secondary data. Data collection methods were carried out using questionnaires and in-depth interviews. The results of the study showed that socialization has a significant influence on public perception and knowledge about Islamic Banks. The better the socialization carried out, the better the public perception and knowledge about Islamic Banks